APLIKASI SMS GATEWAY SEBAGAI REMINDER JADWAL SIDANG DALAM PERKARA PERDATA (Study Kasus : Pengadilan Negeri Metro Kelas IB) - Muhammad Adie Syaputra; Cacah Firmansyah (Institut Informatika dan Bisnis Darmajaya, 2019)
At this time the process of calling the party related to the trial process in the Metro District Court was still carried out by calling on the Jurusita with a relatively long period of time from the stipulated trial schedule. SMS gateway is an application for utilizing SMS facilities, SMS gateway is a gateway that connects computers and clients via SMS. From the problems faced, the SMS gateway technology is applied in the trial schedule reminder system using the GAMMU application and PHP programming, so that the trial schedule information can be sent by the administrator via scheduled SMS (Short Message Service) messages on the scheduled day to the user. GAMMU is a cross-platform application that is used to bridge / communicate between SMS gateway databases with SMS devices. The GAMMU application is a daemon that runs in the background. Every time, GAMMU monitors SMS devices and the SMS gateway database. When there is an SMS entered into SMS devices, GAMMU immediately moves it into the inbox in the SMS gateway database. The system development method used in this study is the waterfall method which is often called the classic life cycle, which illustrates a systematic and sequential approach to software development from top to bottom. With the SMS gateway application, the calling process is more effective because the user is reminded again when the trial day has been set so that the user does not attend the trial.